Three by three weeks of robot-enhanced repetitive gait therapy within a global rehabilitation plan improves gross motor development in children with cerebral palsy – a retrospective cohort study. (July 2019) - Weinberger, R.; Warken, B.; König, H.; Vill, K.; Gerstl, L.; Borggraefe, I.; Heinen, F.; von Kries, R.; Schroeder, A.S.
Abstract: Aim: To assess the improvement in gross motor function following three blocks of a three-week, intensive robot-enhanced treadmill therapy (ROBERT-Program). Method: retrospective chart review in a before-after interventional trial in children with cerebral palsy attending a university hospital outpatient rehabilitation centre. Patients received three blocks of a three-week, 12 sessions ROBERT-Program over a mean period of 24 months. Outcome measures were block specific and cumulative improvement in GMFM 66, D and E. Longterm GMFM 66 improvements were compared to the individuals' expected increment as derived from previously published GMFM-66 percentiles. 95% confidence intervals (CI) and paired t-test were calculated. Results: 20 children (8 GMFCS Level II; 12 GMFCS Level III, mean age 5.9 years (CI: [5.0; 6.7])) were treated. For each block a significant increase in motor performance in similar size could be observed without deterioration between blocks. The cumulative improvement during 21 months observation period was: 6.5 (CI: [4.8; 8.2]) in GMFM 66, which represents a clinically meaningful effect size of 3.6 (CI: [1.4; 5.8]) above the expected improvement. Interpretation: Progressive clinically meaningful improvement in motor performance for three blocks of ROBERT-Program was observed. Cumulative GMFM 66 improvements exceeded the individuals' age-specific expected course. Highlights: Before and after comparison of robot-enhanced treadmill therapy (ROBERT). Effects of each three-week ROBERT block and cumulative effects of three blocks. Clinically meaningful improvements in gross motor function after each block. Three blocks yielded a higher increase in GMFM 66 than expected with standard care. Robot-assisted intense gait therapy may boost motor development in children with CP.